The Capital Liberation of the Limited Liability Company - Boukhors, Abdelaziz; Bendib, Hamza (Journal of Legal Studies and Researches, 2022)
This study examines the rules related to the capital liberation of the limited liability company. The paper is an attempt to evaluate the amendments of Law No. 15-20 and the link between the various Regulations for this type of company. The study requires two main sections: the first examines seed capital liberation and the second examines the liberation of the capital in the case of increasing.